INFORMASI DIAGNOSTIK GAMBARAN RADIOGRAF CERVICAL HASIL MULTIPLANAR RECONSTRUCTION CT-SCAN KEPALA - Panji Wibowo Nurcahyo; Merliana Devina; Akhmad Haris Sulistiyadi; Siti Daryati (JRI (Jurnal Radiografer Indonesia), 2021)
ABSTRACT Introduction : Data at Kenyatta National Hospital (KNH) from 2012 to 2016 recorded that there were 1,432 patients with a head injury diagnosis. Of the patients diagnosed with moderate or severe head injury, 11 (3.07%) patients had head and neck injuries. The clinical pathway in the diagnosis of head injury, CT-Scan of the brain (preferably with the inclusion of the cervical vertebrae) is now the rule in assessing traumatic brain injury. At the Radiology Installation of the Salatiga City Hospital, a head CT scan with a head injury diagnosis used a scan of the area from cervical 7 to the vertex, then cervical radiographs were made using MPR. Methods : This study uses a qualitative method with a case study approach. Data collection was carried out in March 2020 by direct observation, in-depth interviews, and documentation studies.Results : Patients diagnosed with CKS and CKB were shown cervical MPR. This MPR image has no superposition, which usually shows cervical 1 and 2 superposition with the mandible even at an angle, and in the lateral projection, cervical 7 superposition with the shoulder. The disadvantage is that the radiation dose received by the patient increases, but on radiological examination there is a justification principle, namely even though using a CT-Scan with greater radiation, the benefits obtained are also greater. In addition, burst fractures can be seen on cervical radiographs from MPR. There are fractures in trauma victims that are not fully demonstrated on radiographs at cervical 1 to cervical 2, cervical 6 to 7 cervical levels, and most involve the transverse process because the patient is uncooperative. Helical CT scanning can depict significant fractures that cannot be demonstrated on conventional radiographs and should be added to the initial screening for suspected cervical trauma.Conclusion : The cervical MPR image aims to obtain four cervical projections, namely AP, lateral, right oblique, and left oblique without conventional projections with the aim of minimizing movement in patients who are at risk of aggravating spinal cord injury. Diagnostic information from MPR results is to obtain structural visualization. specific, determine the extent of the lesion, localize the lesion and bone fragments. However, the radiation dose received is greater than conventional radiographic examinations.